COVID-19 mortalities in England and Wales and the Peltzman offsetting effect. Issue 60 (26th December 2021) - Williams, Sam; Crookes, Alasdair; Glass, Karli; Glass, Anthony J.
ABSTRACT: There are two approaches to measuring COVID-19 deaths – 'COVID associated deaths' and 'excess deaths'. An excess deaths framework is preferable, as there is measurement error in COVID associated deaths, due to issues relating to imperfect information about deaths that are directly attributable to COVID-19. The standard measure of excess deaths (comparison of deaths to a 5-year average) is subject to an omitted variables problem, as it attributes the entirety of the variation in mortality to COVID-19. We propose a method to estimate a refined measure of COVID-19 excess deaths in England and Wales that addresses the omitted impact of the first blanket lockdown. Using the counterfactual, we obtain a first stage estimate of excess deaths. In the second stage, this is decomposed into estimates of a refined measure of COVID-19 excess deaths and the excess mortality impact of lockdown. Our results suggest: (i) a refined estimate of mean weekly COVID-19 excess deaths that is 63% of standard excess deaths; and (ii) a positive net excess mortality impact of the lockdown. We make a case that (ii) is due to the Peltzman offsetting effect, i.e. the intended mortality impact of the lockdown was more than offset by the unintended impact.